In vitro and in silico evaluation of fucosterol from Sargassum horridum as potential human acetylcholinesterase inhibitor. Issue 12 (13th August 2019) - Castro-Silva, E. S.; Bello, M.; Hernández-Rodríguez, M.; Correa-Basurto, J.; Murillo-Álvarez, J. I.; Rosales-Hernández, M. C.; Muñoz-Ochoa, M.
Abstract: The fucosterol has been reported numerous biological activities. In this study, the activity in vitro of the fucosterol from Sargassum horridum as potential human acetylcholinesterase inhibitor was evaluated. The structural identification was obtained by nuclear magnetic resonance (NMR) spectroscopy and based on experimental data, we combined docking and molecular dynamics simulations coupled to the molecular-mechanics-generalized-born-surface-area approach to evaluating the structural and energetic basis for the molecular recognition of fucosterol and neostigmine at the binding site of acetylcholinesterase (AChE). In addition, the Lineweaver–Burk plot showed the nature of a non-competitive inhibition. The maximum velocity ( V max ) and the constant of Michaelis–Menten ( K m ) estimated for fucosterol (0.006 µM) were 0.015 1/ V o (Δ A / h and 6.399 1/[ACh] mM −1, respectively. While, for neostigmine (0.14 µM), the V max was 0.022 1/ V o (Δ A / h ) and Km of 6.726 1/[ACh] mM −1, these results showed a more effective inhibition by fucosterol respect to neostigmine. Structural analysis revealed that neostigmine reaches the AChE binding site reported elsewhere, whereas fucosterol can act as a no-competitive and competitive acetylcholinesterase inhibitor, in agree with kinetic enzymatic experiments. Binding free energy calculations revealed that fucosterol reaches the acetylcholinesterase binding site with higher affinity than neostigmine, which is according to experimental results. Whereas the per-residue decomposition free energy analysis let us identify crucial residues involved in the molecular recognition of ligands by AChE. Results corroborate the ability of theoretical methods to provide crucial information at the atomic level about energetic and structural differences in the binding interaction and affinity from fucosterol with AChE. Communicated by Ramaswamy H. Sarma